About new oil and gas prospects of the Antarctic margin - V. D. Solovyov; V. G. Bakhmutov; I. N. Korchagin; S. P. Levashov; N. A. Yakymchuk; D. N. Bozhezha (Ukrainian Antarctic Journal, 2010)
The results of investigations in 2006-2010 for oil and gas in the Antarctic Peninsular region are given. In 2004 and 2006, the geoelectric research by methods of forming a short-pulsed electromagnetic field (FSPEF) and vertical electric-resonance sounding (VERS) have been conducted from shipboard in this region. The "deposit" type anomaly was mapped by FSPEF survey, and anomalous polarized layers of "hydrocarbon deposit" type were chosen by VERS sounding within this anomaly on Antarctic margin. The anomalous zones of “oil deposit” type were mapped also on Antarctic Peninsular margin in the region of UAS "Academician Vernadsky" and anomalous zones of “gas hydrate deposit” type were revealed at the South Shetland margin. The investigation results confirm the high oil and gas potential of the West Antarctica region. The special technology of satellite data processing and interpretation can be used for the hydrocarbon accumulations prospecting and exploration in remote regions such as Antarctic and Arctic areas.